FAKTOR-FAKTOR YANG MEMPENGARUHI KEUNTUNGAN PETANI DALAM USAHATANI SALAK - Bagas Dian Susanto; Lasmono Tri Sunaryanto (Jurnal Sosial Ekonomi Pertanian, 2019)
This research was purposed to; 1) Knowing the effect of the selling price, labor costs, seed costs, fertilizer costs on the profit of salacca farmers, and 2) knowing the variable which has the strongest influence on the profit of the salacca farmers. The research location at Kaliurang village, Srumbung subdistrict, Magelang district. The research quantitative descriptive type. The results of research show that; 1) Selling price (X1), labour cost (X2), seed cost (X3) and fertilizer cost (X4) simultaneously have significant effect on profit (Y). 2) Labour cost (X2) and fertilizer cost (X4) have a partially significant effect on profit while the selling price (X1) and seed cost (X3) no have significant effect on profit. 3) Labour cost (X2) variable has the greatest influence on profit (Y)